Vaccination-Challenge Trials in Beagle Dogs Using Whole-Cell Leptospira interrogans Serovar Copenhageni Vaccine: Prevention of Clinical Leptospirosis, Serological, Leptospiremia, Leptospiruria, Cytokines, Hematological, and Pathological Changes - Teola Noel; Rod Suepaul; Abiodun A. Adesiyun (Pathogens)
A killed, whole-cell vaccine was produced to induce immunity in dogs against leptospirosis. The vaccine, containing serovar Copenhageni, was produced and administered to 12 beagle dogs at both 8 and 12 weeks of age. Ten unvaccinated dogs of the same age group served as the control group. A live, virulent inoculum of Leptospira (1.52 × 109–4.40 × 109 leptospires per dog) was used to challenge the dogs at 2 weeks (Study 1) and 14 months (Study 2) post-booster vaccination. At regular intervals, pre- and post-challenge (PC), the microscopic agglutination test (MAT) was performed to measure antibody titers. Leptospiremia and leptospiruria were determined via culture, and the cytokine, biochemical, and pathological profiles of vaccinates and controls were also assessed. A high antibody response was measurable after booster administration. In Study 1 (onset of immunity), acute leptospirosis was observed in five (100%) out of five unvaccinated dogs. In contrast, no acute clinical leptospirosis developed in vaccinated dogs, except in one (20%) dog with mild clinical signs. In Study 2 (duration of immunity), mild clinical signs were observed in two (40%) of the control dogs, while all vaccinated dogs remained clinically normal. The incidence of leptospiruria and leptospiremia PC was lower in the vaccinated dogs compared to the unvaccinated group. Severe thrombocytopenia occurred in 100% (5/5) of the unvaccinated dogs in Study 1 that exhibited acute severe leptospirosis, whereas 80% (4/5) of the unvaccinated dogs in Study 2 showed mild to moderate thrombocytopenia 3 days after challenge. Four out of five unvaccinated dogs (80%) in Study 1 exhibited icteric tissues and hemorrhages in the lungs and mucosal surfaces of the stomach and intestines. A high IL-10 to TNF-α ratio, observed in the control group of both studies, and severe thrombocytopenia observed in the control group of Study 1, indicative of acute leptospiral disease, were detected. The vaccine prevented acute clinical leptospirosis and reduced the renal carrier state in beagle dogs, and further investigation is required using a larger sample size.